Persepsi Siswa terhadap Kompetensi Pedagogik Guru di SMK Negeri Kabupaten Tanah Datar - Dwi Wulandari; Elizar Ramli (Universitas Negeri Padang, 2019)
This research is motivated by problems in the pedagogical competencies of teachers in SMK Negeri Kabupaten Tanah Datar. This study aims to explore information about teachers pedagogic competencies in SMK Negeri Kabupaten Tanah Datar based on student perceptions in aspect 1) understanding students, 2) implementing learning that is educational and dialogic, 3) utilizing learning technology, 4) implementing learning evaluation, and 5) developing students to actualize various potentials they have. This type of research is descriptive research, with the aim of expressing a situation as it is. The study population was students in SMK Negeri Kabupaten Tanah Datar of flat land totaling 3.436 students. A sample of 99 students was taken using a simple random sampling technique. Data collection instrument is a likert scale model questionnaire with five answer choices. The result showed that the teachers pedagogical competence was basedon the perceptions of the students in 1) understanding the student with an average score of 4,04 in the high category, 2) the implementation of education and dialogical learning with an average score of 3,98 in the high category, 3) utilizing learning technology with an average score of 3,86 in the high category, 4) carrying out evaluation of learning outcomes with an average score of 4,15 in the high category, and 5) developing students to actualize the various potentials they have with the average score of 4,14 is in the high category. Overall, the average score is 4,04 in the high category. The Key word: Perceptions, Pedagogic competence, teacher